Kesiapan Kerja Karyawan Room Division pada Era Artificial Intelligence Peran AI Literacy dan Digital Competence - Adi Robith Setiana; ER Ummi Kalsum; Rohman Agus Jatnika (Journal of Management and Social Sciences, 2026)
This study aims to analyze the effects of AI literacy and digital competence on the work readiness of room division employees at star-rated hotels in Tasikmalaya Regency. A quantitative approach with an explanatory survey design was employed, involving 110 employees selected through purposive sampling. Data were collected using a closed-ended questionnaire based on a five-point Likert scale, distributed through Google Forms and direct administration, and analyzed using Structural Equation Modeling–Partial Least Squares with SmartPLS. The results indicate that AI literacy has a positive and significant effect on work readiness, with a path coefficient of 0.381, while digital competence also has a positive and significant effect, with a path coefficient of 0.472. The R-square value of 0.647 shows that both variables explain 64.7% of the variance in employee work readiness. Digital competence emerged as the more dominant factor in enhancing work readiness. These findings imply that hotel management should integrate digital competence and AI literacy training, strengthen employees’ understanding of data ethics and security, and provide continuous assistance to support effective adaptation and human–AI collaboration.